Adenosine A2A receptor binding profile of two antagonists, ST1535 and KW6002: consideration on the presence of atypical adenosine A2A binding sites - Riccioni, Teresa; Leonardi, Fabiana; Borsini, Franco (Frontiers in Psychiatry, 2010)
Adenosine A2A receptors seem to exist in typical (more in striatum) and atypical (more in hippocampus and cortex) subtypes. In the present study, we investigated the affinity of two adenosine A2A receptor antagonists, ST1535 [2 butyl -9-methyl-8-(2H-1,2,3-triazol 2-yl)-9H-purin-6-xylamine] and KW6002 [(E)-1,3-diethyl-8-(3,4-dimethoxystyryl)-7-methyl-3,7-dihydro-1H-purine-2,6,dione] to the “typical” and “atypical” A2A binding sites. Affinity was determined by radioligand competition experiments in membranes from rat striatum and hippocampus. Displacement of the adenosine analog [3H]CGS21680 [2-p-(2-carboxyethyl)phenethyl-amino-5’-N-ethylcarbox-amidoadenosine] was evaluated in the absence or in the presence of either CSC [8-(3-chlorostyryl)-caffeine], an adenosine A2A antagonist that pharmacologically isolates atypical binding sites, or DPCPX (8-cyclopentyl-1,3-dipropylxanthine), an adenosine A1 receptor antagonist that pharmacologically isolates typical binding site. ZM241385 [84-(2-[7-amino-2-(2-furyl) [1,2,4]-triazol[2,3-a][1,3,5]triazin-5-yl amino]ethyl) phenol)] and SCH58261 [(5-amino-7-(β-phenylethyl)-2-(8-furyl)pyrazolo(4,3-e)-1,2,4-triazolo(1,5-c) pyrimidine], two other adenosine A2A receptor antagonists, which were reported to differently bind to atypical and typical A2A receptors, were used as reference compounds. ST1535, KW6002, ZM241385 and SCH58261 displaced [3H]CGS21680 with higher affinity in striatum than in hippocampus. In hippocampus, no typical adenosine A2A binding was detected, and ST1535 was the only compound that occupied atypical A2A adenosine receptors. Present data are explained in terms of heteromeric association among adenosine A2A, A2B and A1 receptors, rather than with the presence of atypical A2A receptor subtype.